Highly efficient adsorptive and photocatalytic degradation of dye pollutants over biomass-derived carbon-supported Ag composites under visible light. Issue 6 (December 2021) - Mu, Yu; Yang, Saiyu; Li, Yucheng; Zhang, Jianpan; Ma, Mengshao; Wang, Jianlin; Yu, Zhiyi; Ren, Zhaodi; Liu, Jing
Abstract: In this work, biomass-derived carbon-supported (Ag/P@BC) Ag composites were prepared and used to remove pollutants (rhodamine B, RhB) under visible light irradiation. Corn straw was chosen as the source of biomass-derived carbon, and the optimal calcination temperature was set to 600 °C. When AgNO3 with an impregnation concentration of 1.0 mM 1Ag/P@BC (1Ag/P@BC) and RhB with an initial concentration of 320 mg L −1 were added, RhB removal exceeded 93%, and the removal capacity reached 1536.71 mg g −1 after adsorption and photocatalysis for 60 min. The maximum capacity of 3141.73 mg g −1 was achieved for RhB removal over 1Ag/P@BC. Although 1Ag/P@BC presents the greatest removal capacity (including adsorption–photocatalysis), 0.1Ag/P@BC had the lowest bandgap energy (2.14 eV) and the highest photocatalytic activity. Owing to its large specific surface area (1655.02 m 2 g −1 ), 0.1Ag/P@BC had a photodegradation rate 33 times that of pure BC, as determined from kinetic studies. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and high-resolution transmission electron microscopy (HRTEM) analyses revealed that both Ag and Ag3 PO4 existed in the composites and that an electronic interaction occurred between P and O, which was attributed to Ag loading. Moreover, the composites have good stability and broad applicability in acidic, neutral and alkaline conditions as well as in tap water. Based on the photoluminescence (PL), electrochemical impedance spectroscopy (EIS), electron spin resonance (ESR) and trapping experiment results, an in-depth analysis of the underlying mechanism for the adsorption–photocatalysis process was also conducted. Graphical Abstract: ga1 Highlights: A novel biomass-derived carbon-supported Ag composites (Ag/P@BC) was successfully fabricated. The photodegradation rate of RhB over Ag/P@BC was 33 times higher than that over pure BC. Ag atoms in the composites act as charge carrier recombination centers, thus promotes the separation eﬃciency of e − /h + . An in-depth analysis of the mechanism underlying the adsorption–photocatalysis process was conducted.